Development of nanofibrous membranes incorporating WO3/TiO2/Ag3PO4 photocatalysts for the degradation of methylene blue - Nien, Yu-Hsun; Huang, Ting-Yu (Journal of polymer research, 2025)
In this study, WO 3 /TiO 2 and WO 3 /TiO 2 /Ag 3 PO 4 photocatalysts with different ratios were prepared using the sol-gel and precipitation methods. Additionally, to facilitate the recovery of photocatalysts from water, nylon 6,6 nanofiber membranes containing the photocatalysts (NFMWTAP) were fabricated using electrospinning and electrospray techniques. The adsorption and degradation of methylene blue under visible light were compared for different ratios of photocatalysts. The results showed that among the WO 3 /TiO 2 samples with different weight percentages, 3 wt% WO 3 /TiO 2 exhibited the highest methylene blue removal efficiency. Therefore, we synthesized WO 3 /TiO 2 /Ag 3 PO 4 ((W/T)-(AP)) photocatalysts with different weight percentages using 3 wt% WO 3 /TiO 2 as the base catalyst. When the ratio of WO 3 /TiO 2 to Ag 3 PO 4 was 5:5, the removal efficiency was the highest, achieving a dye removal rate of 99.60%. Meanwhile, the nylon 6,6 nanofiber membrane containing the photocatalyst achieved a dye removal rate of 99.18% after 30 min of dark adsorption followed by 1 h of visible light irradiation. Even after three cycles of reuse, the dye removal rate remained as high as 97.86%.